2013
DOI: 10.4028/www.scientific.net/kem.554-557.248
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Fast Calculation Model for the Process Monitoring of Open Die Forging Processes

Abstract: To provide a high quality of forged products, a homogeneous distribution of material properties has to be achieved inside the ingot. As the properties are not visible from the outside, an online monitoring during the forging process is required. By using modern measuring equipment and fast calculation models, the equivalent strain, temperature and average grain size in the core fibre of a forging ingot can be calculated parallel to the process. Software implementing the fast calculation models has been establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In order to do that, in the case of forging sequence design and optimization, it is necessary to simulate many different configuration corresponding to different forging strategies in order to identify the best solution. FEM is one of the most commonly adopted approach, anyway, it is reported that it requires significant efforts in terms of both computational resources and time [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to do that, in the case of forging sequence design and optimization, it is necessary to simulate many different configuration corresponding to different forging strategies in order to identify the best solution. FEM is one of the most commonly adopted approach, anyway, it is reported that it requires significant efforts in terms of both computational resources and time [24,25].…”
Section: Introductionmentioning
confidence: 99%